Approximation of the classes Wrβ Hα by three-harmonic Poisson integrals - Kal’chuk, I. V.; Kravets, Vasyl; Кравець, Василь Іванович; Кравец, Василий Иванович; Hrabova, U. Z. (My University, 2020)
We obtain asymptotic equalities for the least upper bounds of deviations of the three-harmonic Poisson integrals from functions of the classes Wrβ Hα in a uniform metric in the case r > 3; 0 ≤ α < 1:
Keywords: Kolmogorov–Nikol’skii problem; three-harmonic Poisson integral; asymptotic equality; Weyl– Nagy derivative; Lipschitz condition